Measurement of two-point energy correlators within jets in p+p collisions at √s = 200 GeV - Aboona, Bassam; Deppner, Ingo Martin; Leung, Yue; Söhngen, Yannick (Physical review letters, 2025)
Hard-scattered partons ejected from high-energy proton-proton collisions undergo parton shower and hadronization, resulting in collimated collections of particles that are clustered into jets. A substructure observable that highlights the transition between the perturbative and nonperturbative regimes of jet evolution in terms of the angle between two particles is the two-point energy correlator (EEC). In this Letter, the first measurement of the EEC at RHIC is presented, using data taken from 200 GeV 𝑝 +𝑝 collisions by the STAR experiment. The EEC is measured both for all the pairs of particles in jets and separately for pairs with like and opposite electric charges. These measurements demonstrate that the transition between perturbative and nonperturbative effects occurs within an angular region that is consistent with expectations of a universal hadronization regime that scales with jet momentum for a given initiator flavor. Additionally, a deviation from Monte Carlo predictions at small angles in the charge-selected sample could result from mechanics of hadronization not fully captured by current models.
Veröffentlicht: 10. September 2025
*STAR Collaboration: B.E. Aboona, I.M. Deppner, Y.H. Leung, Y. Söhngen [und 344 weitere Personen]
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Gesehen am 02.02.2026